2017
DOI: 10.1080/00224545.2017.1373622
|View full text |Cite
|
Sign up to set email alerts
|

Tattoo or taboo? Tattoo stigma and negative attitudes toward tattooed individuals

Abstract: Tattoos are common in the United States; however, tattooed persons may be perceived as having more negative character and as more deviant than people without tattoos. College students (Study 1) and community members (Study 2) viewed images of men and women with tattoos or the same images with the tattoos digitally removed and rated the targets' characteristics. Half of the participants viewed a target with a tattoo, and half viewed that target without it, allowing for both within- (participants all rated one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…While several studies have emphasized how participants negotiated their identities and transcended prevalent taboos and stigmas to adopt products (Piha et al, ; Sandikci & Ger, ; Wilner & Huff, ), this study contributes to the existing body of literature by emphasizing that such transitions are not always possible. Broussard and Harton () found that negative social perceptions persist about tattooed individuals. Muhamed and Mizerski () also found similar results while understanding the consumption of taboo products in the context of religion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While several studies have emphasized how participants negotiated their identities and transcended prevalent taboos and stigmas to adopt products (Piha et al, ; Sandikci & Ger, ; Wilner & Huff, ), this study contributes to the existing body of literature by emphasizing that such transitions are not always possible. Broussard and Harton () found that negative social perceptions persist about tattooed individuals. Muhamed and Mizerski () also found similar results while understanding the consumption of taboo products in the context of religion.…”
Section: Discussionmentioning
confidence: 99%
“…Extant literature on taboo in consumption focuses on three topics—taboo products, communication of such products and taboo trade‐offs (see Table ). Research in taboo products has received the most attention (Amos & Haglund, ; Broussard & Harton, ; Diana, Rachmayanti, Anwar, Khomsan, & Christianti, ; McGraw, Schwartz, & Tetlock, ; Muhamad & Mizerski, ; Nguyen et al, ; Piha et al, ; Yalkin & Veer, ). Studies on this issue identify either how individual consumers have broken away from taboos and divorced themselves from shame and immorality or how taboos have deleteriously affected the consumption of taboo products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 , 8 Almost 30% of people living in the USA now have tattoos. 9 In an Australian context, tattoos depicting the nineteenth-century outlaw or ‘bushranger’ Ned Kelly are often chosen because of his anti-authoritarian actions. Analysis of cases with such tattoos presenting to medico-legal autopsy, however, has revealed that 85% of the deaths were unnatural, including 40% which were due to suicides and 10% which were due to homicides.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, perpetrators may feel a sense of greater power vis-a-vis a visibly tattooed employee. Perpetrators may believe that they can more readily get away with harassment because of the visibly tattooed employee's lower perceived status (Halnon & Cohen, 2006), since those with tattoos are stereotyped as ‘other’ and less intelligent, honest, and capable (Broussard & Harton, 2017; Dean, 2010; Degelman & Price, 2002). This argument is supported by the power differential explanation of sexual harassment which posits that perpetrators are largely motivated by a desire to reinforce a sense of power and escape negative consequences from the organization for their behavior (Stockdale & Nadler, 2012).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%